Ocena efektywności leasingu - Okręglicka, Małgorzata (Opinion of the Efficiency of the Leasing, 2005)
Leasing can be situated as a service on capital market. It is the most often used source of financing for Polish investors except credit and internal capital of enterprises. The proper analysis of leasing efficiency gives information on the kind of enterprise and investment for which it is an optimal solution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 291-300